Electric and Electrochemical Microfluidic Devices for Cell Analysis - Hiramoto, Kaoru; Ino, Kosuke; Nashimoto, Yuji; Ito, Kentaro; Shiku, Hitoshi (Frontiers in Chemistry, 2019)
Microfluidic devices are widely used for cell analysis, including applications for single-cell analysis, healthcare, environmental monitoring, and organs-on-a-chip that mimic organs in microfluidics. Moreover, to enable high-throughput cell analysis, real-time monitoring, and non-invasive cell assays, electric and electrochemical systems have been incorporated into microfluidic devices. In this mini-review, we summarize recent advances in these systems, with applications from single cells to three-dimensional cultured cells and organs-on-a-chip. First, we summarize microfluidic devices combined with dielectrophoresis, electrophoresis, and electrowetting-on-a-dielectric for cell manipulation. Next, we review electric and electrochemical assays of cells to determine chemical section activity, and oxygen and glucose consumption activity, among other applications. In addition, we discuss recent devices designed for the electric and electrochemical collection of cell components from cells. Finally, we highlight the future directions of research in this field and their application prospects.